IMPROVING STUDENTS SPEAKING SKILL THROUGH PROJECT-BASED LEARNING - Ichsan, Muhammad Hunafatul; Apriliaswati, Rahayu; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Absract: This research was conducted to the eleventh grade students of SMA Negeri 3 Sintang in academic year 2015/2016. The aim of this research was to find out how well the use of Project-based learning in improving students? speaking skill. In conducting this research, the writer used Classroom Action Research as the method of research. The writer observed the improvement of students? speaking skill by collecting the data through observation and measurement technique. This research was implemented to 36 eleventh grade students of SMA Negeri 3 Sintang. The findings of this research showed that there was an improvement on students? speaking skill through project-based learning particularly in accuracy and fluency. In the first cycle, the students? mean score was 74.44. In the second cycle, the students? mean score was 78.06. Students? score in third cycle was 81.04. It can be concluded that the students? speaking skill taught using project-based learning was improved. Key words: Project-Based Learning, Speaking, Classroom Action Research   Abstrak: Penelitian ini dilakukan terhadap siswa SMA Negeri 3 Sintang tahun ajaran 2015/2016. Tujuan dari penelitian ini adalah untuk melihat seberapa besar pengaruh project-based learning dalam meningkatan kemampuan berbicara siswa. Untuk menyelesaikan masalah ini, penulis melakukan penelitian tindakan kelas dengan menggunakan metode project-based learning yang diterapkan pada siswa. Penulis mengamati peningkatan siswa melalui teknik measurement dan observasi. Hasil dari peneliitian menunjukkan adanya peningkatan pada kemampuan berbicara siswa. Respon siswa menunjukkan bahwa mereka tertarik untuk belajar berbicara melalui project-based learning. Pada siklus pertama, skor rata-rata siswa adalah 74,44. Pada siklus kedua, skor rata-rata siswa adalah 78,06. Pada siklus ketiga, skor siswa meningkat menjadi 81,04. Dapat disimpulkan bahwa keterampilan berbicara siswa diajarkan menggunakan project-based learning ditingkatkan.   Kata Kunci: project-based learning, speaking, penelitian tindakan kelas